UMA ANÁLISE COMPARATIVA DA CONFORMIDADE COM PARÂMETROS INTERNACIONAIS DE ACESSIBILIDADE EM APLICAÇÕES WEB NA REGIÃO DO BICO DO PAPAGAIO - Castro, Daniel (2023)
In a world that increasingly seeks the inclusion of allhuman beings in daily, professional and cultural activities, itbecomes essential for developers of web envir onments to makedesign choices in this regard. This article aims to comparativelyanalyze pages of public agencies and private companies in theBico do Papagaio region, seeking to identify whether they arefollowing accessibility techniques on the web. To this end, it wasnecessary to review and respect the precepts established by theW3C in its Web Accessibility Guide (better known by theacronym WCAG), which establishes and standardizes processesand practices to be adopted in the process of making the we web experience accessible to all. To carry out the analysis, applications expeexperience accessible to all. To carry out the analysis, applicationsindicated by the W3C itself were used, which can be found andtested for free on the internet. After collecting and analyzing thedata, it was possible to observe which institutions be st suited theparameters or not, as well as which types of limitations are notmet by these sites. Finally, private institutions were more suited tointernational accessibility guidelines when compared to selectedpublic institutions, within the parameters established by theresearch.